TAMSIL METAFISIK DAN PENGALAMAN MISTIK DALAM SAJAK-SAJAK CINTA GANDRUNG KARYA A. MUSTOFA BISRI - B.S, Abdul Wachid (Diksi, 2015)
Mustofa Bisri’s poetry belongs to the category of poetry that stars from meaning itself but it is also composed from esthetic mystical experiences, It does not rely on the beauty of verbal expression and on language play only. Its esthetic quality also lies on the images of esthetic mystical experiences reflected in his poems. Even if translated into another language, the poems would not lose the esthetic quality. In accordance with the theory of poetry, the language used in the poems possesses what is often called deceptive simplicity. And in his poems it is assumed to be the result of the basic nature of poetry, that is, indirect expression by way of displacement of meaning, distortion of meaning, and creation of meaning. Keywords: poetry, mystical experience, esthetic quality.